Solar Calendar, And Other Ways of Marking Time - Bendik-Keymer, Jeremy (punctum books, 2017)
At the end of his life, Pierre Hadot was a professor at the Collège de France - a "professor's professor" - and he helped Michel Foucault, most famously, conceptualize ethics. Hadot devoted his career to recovering the ancient conception of philosophy, according to which the discourses of universities are but a fragment of what philosophy is. His engagement with this theme helped Bendik-Keymer understand and develop a personal counter-culture to his academic work, a kind of original academics truer to the idea of the philosophical school Plato first developed in his Ἀκαδήµεια. But while Plato's school developed a useful form of life, it had an ambivalent relation to democracy and to everyday people. Whereas Plato was in some ways one of the first egalitarians by merit (especially concerning women), he was also deeply classist in his categorization of intellectual potentials. He effectively thought some people were stupid by nature, having no philosophical worth. Hence the Ἀκαδήµεια existed outside the city, in practice exclusive and somewhat sequestered. To some extent, Plato's vision of philosophy - at least as explained by Hadot - had the practical point of philosophy right, but this point still needed to be rendered thoroughly democratic in the polyphony and multiple intelligences of people. Doing so coheres with what Foucault was after in his application of Hadot. It is also what Bendik-Keymer is after - to extract what is good from original academics and make it democratic, as opposed to dumbing people down.